The FOMC attention cycle - David Finck; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2024)
We use a new data set of daily visits of the website of the Federal Reserve Board to study the acquisition of information about monetary policy around meetings of the FOMC.
Keywords: E58; 330; monetary policy; communication; Federal Reserve; information acquisition